Technical and Economic Feasibility Study of rainwater use system in communities in Jardim Gramacho- RJ - Ribeiro, Paula Iglesias; Amario, Mayara; Stolz, Carina Mariane; Najjar, Mohammad; Vazquez, Elaine Garrido (Seven Editora, 2023)
Many Brazilian communities are in a situation of extreme vulnerability, with a lack of decent housing and water supply network, a fundamental element for survival. This article presents the feasibility analysis of the implementation of the rainwater use system designed by the ceiling (social organization that acts to reduce poverty) in the houses built by it in the Rampinha and Chatuba communities, in Jardim Gramacho, through the study of Demand, supply, sizing of reservoirs and prospecting for materials. The results showed that the project is able to supply 67% of the demand for non -potable purposes with a Payback of up to 2.8 years, thus reducing the lack of water on site.DOI: https://doi.org/10.56238/devopinterscie-070